Hyperrealitas Iklan Perspektif Hukum Ekonomi Islam - Mursal Mursal; Neza Tessya Inggrit (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Advertising is not just conveying information about a product (ideas, services and "goods"), but advertising also has the nature of "encouraging" and "persuading people to like, choose, then buy which is then very related to a theory of Baudrillard's hyperreality. The purpose of this study is to determine the hyperreality of shampoo advertisements in the perspective of Islamic economic law. The research method used is qualitative research. The results showed that Islamic principles must be upheld, including in terms of advertising, which must not ignore the norms of Islamic law, including those related to making false reality in an advertisement..